Why the Ukraine Crisis Is the West's Fault: A Historical and Philosophical Perspective. Issue 2 (3rd April 2017) - Peng, Chengyi
ABSTRACT: Most Western commentaries on Ukraine in the past few years have blamed the country's crisis on Russia. However, as John Mearsheimer has pointed out, prime responsibility for Ukraine's dilemma actually lies with the West. This article examines the situation in more depth, providing a historical and philosophical analysis of the reasons why the crisis has been the inevitable outcome of blundering Western actions. On a superficial level, the Ukraine crisis results from NATO (North Atlantic Treaty Organization)/EU (European Union) expansion, from the "democracy" project mounted within Ukraine by the West, from a failure by leading Western countries to consider Russian strategic interests, and from a lack of prudence by key Western figures who have not foreseen the consequences of their actions. On a deeper level, the West under the leadership of the United States has proven unable to learn from similar mistakes in the past, or to display insight into the flaws within its political norms. Worst of all, the West has fallen into the trap, which Thucydides correctly discerned in relation to the expansion of Athenian imperialism and its eventual demise. Various key insights of Thucydides and Spinoza are adduced to support this interpretation.